2006
DOI: 10.1016/j.nurx.2006.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurorestorative treatment of stroke: Cell and pharmacological approaches

Abstract: Summary:There is a compelling need to develop cell and pharmacological therapeutic approaches to be administered beyond the hyperacute phase of stroke. These therapies capitalize on the capacity of the brain for neuroregeneration and neuroplasticity and are designed to reduce neurological deficits after stroke. This review provides an update of bone marrowderived mesenchymal stem cells (MSCs) and select pharmacological agents in clinical use for other indications that promote the recovery process in the subacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 120 publications
(135 reference statements)
1
115
0
Order By: Relevance
“…Recent research has suggested that an alternative approach for restoring blood flow is to promote angiogenesis in regions surrounding the ischemic brain beyond the hyperacute phase of the stroke. The time window for therapies improving stroke recovery, so called neurorestorative therapies, is likely to be far longer than that for acute neuroprotection (Chen and Chopp, 2006;Beck and Plate, 2009). Neurorestorative events include neurogenesis, synaptic plasticity, and angiogenesis, for which the generation of new blood vessels as a neurorestorative event in the chronic stage after stroke, could be interpreted as a natural defense mechanism helping to restore the supply of nutrients to the affected brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has suggested that an alternative approach for restoring blood flow is to promote angiogenesis in regions surrounding the ischemic brain beyond the hyperacute phase of the stroke. The time window for therapies improving stroke recovery, so called neurorestorative therapies, is likely to be far longer than that for acute neuroprotection (Chen and Chopp, 2006;Beck and Plate, 2009). Neurorestorative events include neurogenesis, synaptic plasticity, and angiogenesis, for which the generation of new blood vessels as a neurorestorative event in the chronic stage after stroke, could be interpreted as a natural defense mechanism helping to restore the supply of nutrients to the affected brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis, primarily in the ischemic boundary zone, enhances the supply of oxygen and nutrients to the affected tissue. Additionally, the generation of new blood vessels facilitates highly coupled neurorestorative processes, including neurogenesis and synaptogenesis, which in turn lead to improved functional recovery (Chen and Chopp, 2006;Beck and Plate, 2009). Studies from human and experimental stroke studies provide evidence for the therapeutic role of angiogenesis after focal cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Such molecules may include neurotrophic growth factors, chemokines, cytokines, and extracellular matrix proteins. The effect of such factors can be very broadly classified as angiogenic, neurogenic, neuroprotective, synaptogenic and inhibition of scarring [63]. Paracrine effects involve direct neurotrophic and/or neuroprotective activity on either resident progenitor cells, hence inducing neurogenesis/ oligodendrogenesis, or protective, anti-apoptotic effects on neurons or glia cells, neurite outgrowth and angiogenesis.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Various animal models of ischemia have been used to investigate the therapeutic effects of MSCs on the lesioned brain and in all these models, bone marrow-derived MSCs resulted in an increased survival of neurons and most of the time in an improved cognitive function of the animals (reviewed in (van Velthoven et al 2009)). In addition, MSCs have been described to reduce the thickness of the scar walls and may also favour angiogenesis Chopp et al, 2008) as well as synaptogenesis (Chen & Chopp, 2006). Functional improvements may be observed whatever the implantation route, intravenously or intracerebrally, even if reduction in infarct volume is not always observed (Li et al, 2000).…”
Section: Adult Cells For Cerebral Ischemia and Traumatic Brain Injurymentioning
confidence: 99%